2021
DOI: 10.1097/prs.0000000000008102
|View full text |Cite
|
Sign up to set email alerts
|

Reduction Mammaplasty for Macromastia in Adolescents: A Systematic Review and Pooled Analysis

Abstract: acromastia, or benign breast hypertrophy, often leads to symptoms that can be debilitating for individuals. These include pain, intertriginous dermatitis, restrictive respiratory effort, self-esteem issues, limitations on activity participation, and others. 1 Preoperatively, patients with macromastia have been shown to have a significantly worse health-related quality of life compared to the normal population. 1 Bilateral reduction mammaplasty is a very common plastic surgery procedure undergone for macromasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…The rate of revision surgery is small, and although patients may experience some postoperative breast growth, it is likely small and does not bring about a recurrence of symptoms. 16 Our analysis confirms this finding as we show obesity is not associated with reoperation rates in the short-term/immediate postoperative period (Table 2). Our analysis agrees with established literature that obesity is likely a risk factor for certain wound complications in reduction mammoplasty.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The rate of revision surgery is small, and although patients may experience some postoperative breast growth, it is likely small and does not bring about a recurrence of symptoms. 16 Our analysis confirms this finding as we show obesity is not associated with reoperation rates in the short-term/immediate postoperative period (Table 2). Our analysis agrees with established literature that obesity is likely a risk factor for certain wound complications in reduction mammoplasty.…”
Section: Discussionsupporting
confidence: 87%
“…Although the overall rate of complication remains low (6.3%), increasing BMI portends increasing risk for superficial SSI. The rate of revision surgery is small, and although patients may experience some postoperative breast growth, it is likely small and does not bring about a recurrence of symptoms 16 . Our analysis confirms this finding as we show obesity is not associated with reoperation rates in the short-term/immediate postoperative period (Table 2).…”
Section: Discussionsupporting
confidence: 84%
“…5,12,13 For adolescents who underwent reduction mammaplasty irrespective of oncoplastic techniques, patients have reported long-term complications. In a study by Hudson et al, 28 21.7% of patients reported having altered nipple sensation. Nuzzi et al 5 found 8.9% of patients having partial hypesthesia of the nipple-areola or breast, and Patel and Corcoran 29 observed 7.8% of patients having partial breast hypesthesia beyond 1 year.…”
Section: Discussionmentioning
confidence: 91%
“…Nuzzi et al 5 found 8.9% of patients having partial hypesthesia of the nipple-areola or breast, and Patel and Corcoran 29 observed 7.8% of patients having partial breast hypesthesia beyond 1 year. These studies by Hudson et al, 28 Nuzzi et al, 5 and Patel and Corcoran 29 did not use oncoplastic techniques, but their implications for long-term outcomes for pediatric patients are relevant. Kraut et al 12 reviewed breastfeeding outcomes of patients with a history of breast reduction surgery and found that the median breastfeeding success was dependent on the subareolar parenchyma preserved: 4% (interquartile range [IQR], 0%–38%) for techniques with no preservation, 75% (IQR, 37%–100%) for techniques with partial preservation, and 100% (IQR, 75%–100%) for techniques with complete preservation.…”
Section: Discussionmentioning
confidence: 99%
“… 11–16 We also had revision rates comparable to or lower than those reported in the literature for thigh lifts (13.6%), 17 mastopexies (12.6%), 18 , 19 abdominoplasties (8.8%), 20 , 21 blepharoplasties (8.5%), 22 facelifts (6.5%), 23 and breast reduction (4.8%). 24 , 25 Despite offering revisions at no cost, eliminating this cost barrier does not appear to manifest a notable increase in the number of revisions provided to patients. Thus, in the context of surgical literature, our revision rates suggest that a no-cost revision policy may not result in a substantial increase in revision surgeries and offer the added benefit of providing reassurance to prospective patients.…”
Section: Discussionmentioning
confidence: 99%